Mai Tawhiti: A Story of Research Collaboration in Aotearoa New Zealand Between a Māori and a Non-Māori Practitioners - Mortensen Steagall, Marcos (School of Art and Design, AUT, 2023)
In recent decades, there has been an emergence of academic discourse about the Global South and Indigenous knowledge internationally, opening opportunities for practice-led research due to the rich epistemologies from Aotearoa. In New Zealand, Māori designers and artists have enriched and redefined the conceptual boundaries of how research is conducted in the academy by providing access to different ways of knowing and alternative methods for leading and presenting knowledge. Despite the exponential growth in global interest in Indigenous knowledge, there remains scant research on creative collaborations between Māori and non-Māori practitioners. Engaging in these collaborative approaches requires adherence to Māori principles to ensure a respectful process that upholds the mana (status, dignity) of participants and the research. This presentation focuses on a collaborative partnership between Māori and non-Māori practitioners that challenges conceptions of ethnicity and reflects the complexity of a globally multi-ethnic society. This presentation was articulated through the poetic photographic installation called 'Tangata Whenua,' supporting a practice-led PhD project entitled 'KO WAI AU? Who am I?'. This project explores how a Māori documentary maker from this iwi (tribe) might sensitively address the grief and injustice of a tragic historical event. In this creative partnership, the researchers collaborated to record the land still bearing the painful remnants of the colonial accounts of the 1866 execution of Toiroa’s ancestor Mokomoko. This presentation contributes to the understanding of cross-cultural and intercultural creativity. It discusses how the shared conceptualization of ideas, immersion in different creative processes, personal reflection, and development over time can foster collaboration.